A novel injury mechanism of trans-styloid palmar-divergent dislocation of the lunate and scaphoid: a case report - Wang, Zhiling; Qu, Junjie; Kang, Le; Cui, Jianqiang; Wang, Yanchao; Li, Chengli; Xu, Lin (Frontiers in Surgery, 2025)
BackgroundPalmar-divergent dislocation of the lunate and scaphoid is a rare high-energy trauma with complex injured mechanism. Early diagnosis and surgery are necessary, however, there is no consensus on surgical treatment, as only a few literatures have been reported.Case summaryA 56-year-old man, following a powerful strike to the dorsal side of left wrist and forearm, complained about swelling, tenderness, and limited motion of the left wrist during the physical examination. According to physical and imaging results, this patient was diagnosed with trans-styloid palmar-divergent dislocation of the lunate and scaphoid, as well as radial diaphysis fracture. We performed open reduction, internal fixation with K-wires, ligament reconstruction, and cast immobilization for 6 weeks, followed by early rehabilitation.ConclusionWe firstly described a novel injury mechanism of trans-styloid palmar-divergent dislocation of the lunate and scaphoid based on the classical Mayfield's mechanism, and reviewed suggestions regarding the optimal treatment of palmar-divergent dislocation of the lunate and scaphoid.